Phylogenetic characterization of norovirus strains detected from sporadic gastroenteritis in Seoul during 2014–2016 - Young Eun Kim; Miok Song; Jaein Lee; Hyun Jung Seung; Eun-Young Kwon; Jinkyung Yu; Youngok Hwang; Taeho Yoon; Tae Jun Park; In Kyoung Lim (Gut Pathogens, 2018)
Abstract Background Phylogenetic analysis of norovirus (NoV) is efficient for tracking NoV transmission. To determine the widespread NoV strains in Seoul, we conducted an extensive phylogenetic characterization of NoV-positives from 1659 diarrheal specimens collected in 2014–2016 for the Seoul NoV-surveillance. Results When the large numbers of NoV partial VP1 genome sequences were analyzed in acute gastroenteritis patients along with the phylogenetic characterization, we could identify molecular epidemiologic patterns based on the genetic characteristics of sporadic NoV strains circulating in Seoul, which could provide a detailed description of the genome-wide and community-wide NoV evolution in each genotype. The average NoV detection rate in our study period was 16.34% that was increased by 7.44% from 13.17% in 2014 to 20.61% in 2016. Prevalence of NoV GI and GII was 4.43% and 93.36%, respectively, and the GII.4, GII.17, and GII.3 were found to be the major type among 17 genotypes of NoV. The most prevalent one was GII.4 (50.92%) that was followed by GII.17 (18.08%) and GII.3 (9.96%). According to an extensive phylogenetic analysis based on partial VP1 sequences of 1008 NoV (276 sporadic, 518 outbreak and 214 reference), pandemic strains of GII.17, GII.4 and GII.3 have emerged in succession during the 2014-2016 Seoul NoV-surveillance. GII.17 emerged as GII.17|Kawasaki323 in 2014, and became the predominant genotype in 2015 with GII.17|2014_Kawasaki lineages (CUHK-NS-616/Kawasaki308). The formerly predominant GII.4 remained high-level with GII.4|2012_Sydney in 2014 and internally replaced to GII.4|2016_Kawasaki194 lineage (NOR-2565/NOR-2558/OH16002) that caused the sporadic NoV explosion since December 2015. Sporadically prevalent GII.3|Hu/Aichio334-13/2013 failed to develop any outbreaks, whereas sporadic GII.3|Hu/3-28/2015/HNZZ/CHN caused heavy outbreaks in Seoul without preparation time since November 2016. Conclusions This is the first extensive phylogenetic study revealing the important events of NoV strains circulating in Seoul. Particularly, our study period from 2014 to 2016 was very dynamic with the emergences of the three main NoV strains (GII.17|2014_Kawasaki, GII.4|2016_Kawasaki194 and GII.3|Hu/3-28/2015/HNZZ/CHN) every year. We are sure that it is hard to detect above findings by simple conventional analysis. Our present study reports a future paradigm of the NoV molecular epidemiology, which might be highly valuable to track new strains and predict oncoming outbreaks.